It wasn't supposed to be a coronavirus: The quest for an influenza A(H5N1)‐derived vaccine and the limits of pandemic preparedness. (27th July 2020) - Dolan, Brian
Abstract: The COVID‐19 pandemic has raised questions about what efforts were made across the world to prepare governments and healthcare systems for such an event. This spotlight article looks at developments made in "pre‐pandemic preparedness planning" following a number of outbreaks of influenza type A virus in 1997. At that time, a specific avian influenza subtype, referred to as A(H5N1), wreaked havoc among fowl but also infected humans through direct transmission. The potential for slight genetic mutations that could make A(H5N1) more infectious, allowing human‐to‐human transmission, presented the threat of a deadly influenza pandemic. As a result, the U.S. government (and others coordinating through the World Health Organization) launched a pandemic preparation plan, including strategies to develop vaccines against A(H5N1) and its genetic lineages each year. This spotlight article discusses the events that led to the specific concern about A(H5N1) among public health officials, as well as early efforts to derive and stockpile an appropriate vaccine to protect against a possible pandemic. This perspective presents the challenges the world has faced, in recent history, in striving to keep one step ahead of pandemic threats.